Fish farming monitoring system / Mohd Badrul Hisham Mohamid Salih - Mohamid Salih, Mohd Badrul Hisham (Faculty of Information Technology and Quantitative Sciences, 2004)
Fish Farming Monitoring System is developed for variety of users such as researchers, fish farmers and others in the area of water quality monitoring to acquire and monitor water quality parameters. Current system mostly used manual data collection and recording method. Thus, these systems are inefficient. Retrieving and storage becomes a problem for water quality related tasks. Beside that, manual sampling method is tedious, time consuming and error-prone. Basically, in this project, water quality related parameters such as pH, water temperature, and ammonia and dissolve oxygen. In this project artificial neural network is being used with the MATLAB function to identify the optimum water quality.